The Importance of the NRG-1/ErbB4 Pathway for Synaptic Plasticity and Behaviors Associated with Psychiatric Disorders - Shamir, Alon (Society for Neuroscience, 2012)
Neuregulin 1 (NRG-1) and its receptor ErbB4 have emerged as biologically plausible schizophrenia risk factors, modulators of GABAergic and dopaminergic neurotransmission, and as potent regulators of glutamatergic synaptic plasticity. NRG-1 acutely depotentiates LTP in hippocampal slices, and blocking ErbB kinase activity inhibits LTP reversal by theta-pulse stimuli (TPS), an activity-dependent reversal paradigm. NRG-1/ErbB4 signaling in parvalbumin (PV) interneurons has been implicated in inhibitory transmission onto pyramidal neurons. However, the role of ErbB4, in particular in PV interneurons, for LTP reversal has not been investigated. Here we show that ErbB4-null (ErbB4(−/−)) and PV interneuron-restricted mutant (PV-Cre;ErbB4) mice, as well as NRG-1 hypomorphic mice, exhibit increased hippocampal LTP. Moreover, both ErbB4(−/−) and PV-Cre;ErbB4 mice lack TPS-mediated LTP reversal. A comparative behavioral analysis of full and conditional ErbB4 mutant mice revealed that both exhibit hyperactivity in a novel environment and deficits in prepulse inhibition of the startle response. Strikingly, however, only ErbB4(−/−) mice exhibit reduced anxiety-like behaviors in the elevated plus maze task and deficits in cued and contextual fear conditioning. These results suggest that aberrant NRG-1/ErbB4 signaling in PV interneurons accounts for some but not all behavioral abnormalities observed in ErbB4(−/−) mice. Consistent with the observation that PV-Cre;ErbB4 mice exhibit normal fear conditioning, we find that ErbB4 is broadly expressed in the amygdala, largely by cells negative for PV. These findings are important to better understand ErbB4's role in complex behaviors and warrant further analysis of ErbB4 mutant mice lacking the receptor in distinct neuron types.